Comparing supply chains of platinum group metal catalysts in internal combustion engine and fuel cell vehicles: A supply risk perspective - Dengye Xun; Xin Sun; Zongwei Liu; Fuquan Zhao; Han Hao (Cleaner Logistics and Supply Chain)
Platinum group metals (PGMs) are important catalytic materials for producing emission after-treatment devices in internal combustion engine vehicles (ICEVs) and fuel cells in fuel cell vehicles (FCVs). There are high resource and technical barriers along the supply chain of PGM catalysts, for which assessing the associated supply risks is essential to understand the potential challenges. This study maps the supply chains of PGM catalysts used in ICEVs and FCVs for the period of 2010–2020, and compares the associated supply risks. The results show that significant supply risks can be identified in both the upstream and downstream stages of PGM catalyst supply chains for ICEV and FCV uses. Specifically, the ICEV-related PGM catalyst supply chain maintained high levels of supply risks with slight decline over the assessed period. With recycling considered, supply risks in the refining stage can be reduced by over 30%. Supply risks embodied in the FCV-related PGM catalyst supply chain were relatively higher, with significant fluctuations during the period 2015–2020. Relevant suggestions are propounded aiming to mitigate supply risks of PGM catalysts used in ICEVs and FCVs.